2016
DOI: 10.1017/thg.2016.75
|View full text |Cite
|
Sign up to set email alerts
|

Twinning and Multiple Birth Rates According to Maternal Age in the City of São Paulo, Brazil: 2003–2014

Abstract: The present study investigates the twinning rates in the city of São Paulo, Brazil, during the years 2003-2014. The data were drawn from the Brazilian Health Department database of Sistema de Informações de Nascidos Vivos de São Paulo-SINASC (Live Births Information System of São Paulo). In general, more information is available on the incidence of twinning in developed countries than in developing ones. A total of 24,589 twin deliveries and 736 multiple deliveries were registered in 140 hospitals of São Paulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 35 publications
(53 reference statements)
4
33
1
3
Order By: Relevance
“…There was no difference in twinning rates between the two cohorts, but the rate in 2015 (1.4%) was higher than in the Brazilian state where Pelotas is located (Rio Grande do Sul) (1.2%) (p = 0.04) and in Brazil as a whole (1.13%) (p = 0.002) from 2011 to 2014. (4) This nding is consistent with the fact that the prevalence of some maternal factors associated with the occurrence of twin pregnancies, such as higher age and obesity, (20,31) increased in Pelotas in the last three decades. The proportion of mothers 35 years or older increased from 9.9% in 1982 to 11.0%, 13.3%, and 14.7% in 1993, 2004, and 2015, respectively.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…There was no difference in twinning rates between the two cohorts, but the rate in 2015 (1.4%) was higher than in the Brazilian state where Pelotas is located (Rio Grande do Sul) (1.2%) (p = 0.04) and in Brazil as a whole (1.13%) (p = 0.002) from 2011 to 2014. (4) This nding is consistent with the fact that the prevalence of some maternal factors associated with the occurrence of twin pregnancies, such as higher age and obesity, (20,31) increased in Pelotas in the last three decades. The proportion of mothers 35 years or older increased from 9.9% in 1982 to 11.0%, 13.3%, and 14.7% in 1993, 2004, and 2015, respectively.…”
Section: Discussionsupporting
confidence: 80%
“…(15)(16)(17)(18) There are still few studies on the epidemiology of twin pregnancies and twin births in Brazil. (4,8,(19)(20)(21)(22) Thus, based on data from the 2004 and 2015 Pelotas Birth Cohorts, this study aimed to describe the prevalence of multiple pregnancies according to maternal characteristics and to compare rst-and second-born twins from the same cohort to each other and to newborns from singleton pregnancies, according to the incidence of unfavorable perinatal outcomes and infant mortality rate (IMR). The use of two populationbased birth cohorts from the same city, eleven years apart, with data collected for each twin separately at the time of birth, allows to estimate change in twin births prevalence and to assess difference of risk according to birth order.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the whole city of São Paulo (Otta et al, 2016), the overall average rates of twin and multiple births per 1000 maternities (%) were 11.96 (7.15 DZ and 4.42 MZ) and 0.36, respectively. Over the whole time period considered, we found that the twin birth rate increased 30.8% from 2003 (10.19%) to 2014 (13.33%).…”
Section: Population Studies On Twinning Ratesmentioning
confidence: 99%
“…The incidence of spontaneous dizygotic twinning is between 1% and 4%[1], which is increasing due to advanced maternal ages and the application of assisted reproductive technologies[2, 3]. Approximately 40% of twins are opposite-sex (OS)[4].…”
Section: Introductionmentioning
confidence: 99%